Statistical Grounding of New National Priorities for the Land Using in the Agrarian Sector - Shchuryk, M. V.; Hudzyk І. V. (Statistics of Ukraine, 2019)
Land resources of the agrarian sector are the most important сomponent of the national wealth of Ukraine. However, the efficiency of their use does not meet the present-day requirements, as it is aimed at the permanent increase in the gross output of agricultural products without taking into account the need for improvement and protection of soils, observing the ontology laws and ecology preservation. Land and agrarian reforms implemented through sharing and privatization of land plots have caused the formation of two largest groups of users and owners of agricultural lands: agroholdings and households. However, small and medium agrarian entities have not been properly developed, as it is done in many EU countries. The transformation of land relations in the domestic agrarian sector was directed to searching an honest landlord which had to be households. However, as follows from the study, true owners of land plots could not be found, as the reforms were implemented with significant violations and abuses. As a result, in many cases owners of land plots became individuals who were not directly related to agricultural lands. Unclaimed land shares and increased numbers of plots left by small owners indicate the failure of the land reform. The owners of agroholdings exploiting their lands to obtain extra profits failed to use the leased lands in an efficient manner, mainly because the profitability of land was achieved without taking into account the need for preserving the soils fertility; the need to respect the laws of ecology and optology preservation is also ignored. The article substantiates the need of introducing new national priorities for the use of agricultural lands, where the formation of small and medium-sized agricultural enterprises should become the key measures. The need for inventory of land plots of the agroindustrial complex by land plot, land owner and land user is demonstrated, which will serve as a roadmap for developing the program of land use in the context of globalization and integration processes. Efficiency enhancement of the existing agrarian entities and creating new ones by analogy with the EU countries should become a new priority of the land use policy. The authors propose to engage the capacities of domestic R&D to setting the priorities of land use in the newly created united territorial communities.